2013
DOI: 10.1021/nl4010783
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-Dependent Interfacial Coulomb Scattering in Atomically Thin Field-Effect Transistors

Abstract: Two-dimensional semiconductors are structurally ideal channel materials for the ultimate atomic electronics after silicon era. A long-standing puzzle is the low carrier mobility (μ) in them as compared with corresponding bulk structures, which constitutes the main hurdle for realizing high-performance devices. To address this issue, we perform a combined experimental and theoretical study on atomically thin MoS2 field effect transistors with varying the number of MoS2 layers (NLs). Experimentally, an intimate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
353
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(395 citation statements)
references
References 44 publications
(132 reference statements)
41
353
0
1
Order By: Relevance
“…S6). Note that the values of the optical mobility determined in the present work are much larger than those measured using transport measurements (21)(22)(23)(24)(25) but similar to the values obtained in a high-k HfO 2 gated field-emission transistor (20,26). Furthermore, our results are also greater than the calculated phonon-scattering-limited value of ∼400 cm 2 /V·s (27).…”
Section: Significancesupporting
confidence: 80%
“…S6). Note that the values of the optical mobility determined in the present work are much larger than those measured using transport measurements (21)(22)(23)(24)(25) but similar to the values obtained in a high-k HfO 2 gated field-emission transistor (20,26). Furthermore, our results are also greater than the calculated phonon-scattering-limited value of ∼400 cm 2 /V·s (27).…”
Section: Significancesupporting
confidence: 80%
“…In general, this unique property of MoS 2 , and 2D materials enables the creation of atomically smooth material sheets and the precise control on its number of molecular layers. The indirect to direct crossover occurs at the mono-layer limit resulting in strong contrast in photoluminescence efficiency between mono-and multi-layer sheets [15][16] [27][28][29][30]. The atomically-thin mono-or multi-layer MoS 2 allows excellent gate electrostatics to suppress short channel effects (SCE), which is one of the major issues in scaled MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, l in monolayer MoS 2 reported in early studies was lower than 10 cm 2 V À1 s À1 , 26 but it was later shown that the use of graphene contact and h-BN encapsulation could enhance the measured l in monolayer MoS 2 above 1000 cm 2 V À1 s À1 , 27 and even as high as 34 000 cm 2 V À1 s À1 for six-layer MoS 2.…”
mentioning
confidence: 97%